A novel coating method to reduce membrane infolding through pre-crimping of covered stents – Computational and experimental evaluation. (June 2022) - Ong, Chi Wei; Kumar, Gideon Praveen; Zuo, Keping; Koh, Li Buay; Charles, Christopher J.; Ho, Pei; Leo, Hwa Liang; Cui, Fangsen
Abstract: A covered stent has been used to treat carotid artery stenosis to reduce the chance of embolization, as it offers improved performance over bare-metal stents. However, membrane infolding of covered stents can affect efficiency and functionality for treating occlusive disease of first-order aortic branches. In order to mitigate the degree of infolding of the stent once it was re-expanded, we proposed a new coating method performed on the pre-crimped stent. A systematic study was carried out to evaluate this new coating technique: a) in vivo animal testing to determine the degree of membrane infolding; b) structural finite element modeling and simulation were used to evaluate the mechanical performance of the covered stent; and c) computational fluid dynamics (CFD) to evaluate hemodynamic behavior of the stents and risk of thrombosis after stent deployment. The degree of infolding was substantially reduced as demonstrated by the in vivo deployment of the pre-crimped stent compared to a conventional dip-coated stent. The structural analysis results demonstrated that the membrane of the covered stent manufactured by conventional dip-coating resulted in a large degree of infolding but this could be minimized by our new pre-crimped coating method. CFD studies showed that the new coating method reduced the risk of thrombosis compared to the conventional coating method. In conclusion, both simulation and in vivo testing demonstrate that our new pre-crimped coating method reduces membrane infolding compared with the conventional dip-coating method and may reduce risk of thrombosis. Highlights: A new coating method is proposed for covered stent fabrication to mitigate membrane infolding. Both finite element structural analysis and hemodynamic fluid analysis show improved performances. In vivo testing shows the effectiveness of new coating method. The new coating method can be used for covered stent production.